Weed Management through Pre and Post-emergence Herbicides in Groundnut - Rabari, Prakash; Hatti, Veeresh; Jat, J. R.; Kumar, Vikash (International Journal of Bio-resource and Stress Management, 2024)
A field experiment was conducted at Agronomy Instructional Farm, Department of Agronomy, Chimanbhai Patel College of Agriculture, Sardarkrushinagar Dantiwada Agricultural University, Sardarkrushinagar, Banaskantha (North Gujarat Agro-climatic Zone of Gujarat) during June–October, 2021 to assess the effect of pre- and post-emergence herbicides on weed control in groundnut crop using Randomized Block Design with ten treatments and four replications. Among different weed management practices, two hand weeding at 20 and 40 DAS recorded significantly higher number of pods per plant, resulted in significantly higher pod yield and haulm yield (23.70, 1980 kg ha-1 and 3082 kg ha-1, respectively) which was found at par with interculturing and hand weeding at 15 and 30 DAS (22.90, 1892 kg ha-1 and 2950 kg ha-1, respectively), post-emergence application of sodium acifluorfen 16.5+clodinafop-propargyl 8 EC @ 165+80 g ha-1 (22.53, 1835 kg ha-1 and 2864 kg ha-1, respectively) and imazethapyr 35 WG+imazamox 35 WG @ 70 g ha-1 (21.93, 1800 kg ha-1 and 2811 kg ha-1, respectively) due to better weed control of weeds as indicated by significantly lower density of sedges, grasses, broad leaf weeds and total weeds as evidenced by correlation and regression analysis between total weed density at 60 DAS, at harvest with the pod yield. Whereas, significantly lower number of pods per plant, pod yield and haulm yield at harvest were observed under unweeded check (10.30, 846 kg ha-1 and 1333 kg ha-1, respectively) due to significantly higher density of sedges, grasses, broad leaf weeds and total weeds observed in unweeded check.